TRANSFORMASI DIGITAL MELALUI SMART GOVERNMENT DALAM MENINGKATKAN KINERJA LINGKUNGAN KERJA PEMERINTAHAN - Rizka Ramadani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Digital transformation in the public sector has become a strategic necessity to improve bureaucratic effectiveness, public service quality, and governmental organizational performance. This study aims to analyze the implementation of smart government in improving the performance of the governmental work environment through a Systematic Literature Review (SLR) approach. This research employed a qualitative method by reviewing various national and international scientific articles obtained from Google Scholar, Scopus, ScienceDirect, and IEEE Xplore published between 2020 and 2025. The findings indicate that the implementation of smart government significantly affects organizational performance through organizational effectiveness, operational efficiency, transparency, accountability, public service responsiveness, and organizational agility. Digital transformation also encourages changes in the governmental work environment to become more flexible, collaborative, innovative, and technology-based. The success of smart government implementation is influenced by digital infrastructure readiness, human resource competencies, governance systems, data security, and inter-agency coordination. However, the implementation of smart government still faces several challenges, including limited digital infrastructure, low digital competence among government employees, organizational resistance to change, and data security issues. Therefore, strengthening digital infrastructure, improving the digital competencies of government personnel, and developing integrated digital governance are necessary to support effective and sustainable governmental transformation.Keywords: smart government, digital transformation, organizational performance, public sector, public service